2017
DOI: 10.4209/aaqr.2016.09.0397
|View full text |Cite
|
Sign up to set email alerts
|

Using Box Modeling to Determine Photodegradation Coefficients Describing the Removal of Gaseous Formaldehyde from Indoor Air

Abstract: Human exposure to volatile organic compounds (VOCs) indoors is receiving increasing attention. Formaldehyde (HCHO) is the most common VOC emitted from household materials and is associated with many health risks, including sick building syndrome. In this study, a simple box model was developed and applied to help understand the fate and degradation mechanisms of HCHO in the indoor environment. The model was validated using observations from an air handling system under different conditions. A UV/TiO 2 filter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…4(B), the gaseous HCHO level in the air was rapidly reduced to a safe level in the fast discharge mode; but the other observation needed more time to achieve a similar level in the slow release mode. Our previous study demonstrated the temperature and relative humidity of indoor air are not sensitive to HCHO removal via natural dissipation and photo-degradation (Lin et al, 2017). However, the time course of gaseous HCHO removal presented a photo-regulated phenomenon by switching the illumination environment.…”
Section: Effects Of Pollutant Emitting Modes On Indoor Air Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…4(B), the gaseous HCHO level in the air was rapidly reduced to a safe level in the fast discharge mode; but the other observation needed more time to achieve a similar level in the slow release mode. Our previous study demonstrated the temperature and relative humidity of indoor air are not sensitive to HCHO removal via natural dissipation and photo-degradation (Lin et al, 2017). However, the time course of gaseous HCHO removal presented a photo-regulated phenomenon by switching the illumination environment.…”
Section: Effects Of Pollutant Emitting Modes On Indoor Air Qualitymentioning
confidence: 97%
“…The lighting would increase the air temperature and indirectly enhance the vaporized rate of HCHO from the supported material into the air. Real absorbents have pores of various sizes; the diffusion plays an increasingly important role to decrease the observed activation energy, and the reaction order approaches unity (Lin et al, 2017).…”
Section: Effects Of Pollutant Emitting Modes On Indoor Air Qualitymentioning
confidence: 99%
“…For instance, formaldehyde is the most common VOC released from households and is related to many health risks, including sick building syndrome. Photocatalytic materials were also proven to be effective for degradation of these contaminants [95]. After UV irradiation with a TiO 2 filter for 2 hours, the removal efficiency of gaseous formaldehyde increases to approximately 90%.…”
Section: Volatile Organic Compounds (Voc) Removalmentioning
confidence: 99%
“…Some research studies clarified that TiO 2 NPs with a high surface area have a powerful ability for HCHO photodegradation due to their n-type semiconductor feature. Besides, as a typical photocatalytic oxidation reaction, photodegradation of the indoor pollutant HCHO has been realized by TiO 2 , where the catalytic capability is affected by many factors especially temperature. According to the Arrhenius’ law, a higher temperature could promote the adsorption capacity of gas molecules to anchor onto the catalyst surfaces and accelerate the degradation rate. , To design and fabricate an integrated system with heat-supply and photocatalytic ability is an effective and novel method to achieve the efficient degradation of HCHO gas. Therefore, the MEPCM microcapsules in this research can be built as a platform for the effective photocatalysis of HCHO.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Arrhenius' law, a higher temperature could promote the adsorption capacity of gas molecules to anchor onto the catalyst surfaces and accelerate the degradation rate. 49,50 To design and fabricate an integrated system with heat-supply and photocatalytic ability is an effective and novel method to achieve the efficient degradation of HCHO gas. Therefore, the MEPCM microcapsules in this research can be built as a platform for the effective photocatalysis of HCHO.…”
Section: Stability Of the Pickering Emulsion And Psd Ofmentioning
confidence: 99%